Sensitivity of two dynamical cores in RegCM4.7 to the 2012 intense rainfall events over West Africa with focus on Lau, Nigeria. (2nd September 2020) - Adeniyi, Mojisola Oluwayemisi
ABSTRACT: The two dynamical cores in the Regional Climate Model (RegCM4.7) are evaluated for their skill in simulating intense precipitation over Nigeria during July–September, 2012 by comparing the simulations with Tropical Rainfall Measuring Mission 34B2 version 7 daily and 3 hourly precipitation and Climate Prediction Centre global daily precipitation data. The two cores fairly simulate the rainfall intensity over Nigeria in July, August and September 2012. However, there are sometimes shifts in the locations of flood events. The hydrostatic core performs better. Based on the flooding event of 3 September 2012 at Lau, Karim Lamido local government area (9.2083°N, 11.2754°E) of Taraba State, low outgoing longwave radiation, cyclonic circulation, positive advection and high moisture flux prevail on the days with flooding record. The RegCM4.7 is recommended for use in modeling and downscaling of climate projections over Nigeria with the use of hydrostatic core coarse resolution simulations as a boundary for nesting non-hydro high-resolution simulations.